Uncertainty analysis of toxic gas leakage accident in cogeneration high temperature gas-cooled reactor - Hiroyuki SATO (The Japan Society of Mechanical Engineers, 2019)
An uncertainty analysis method for control room habitability under toxic gas leakage accidents in cogeneration high temperature gas-cooled reactor (HTGR) is proposed to support risk-informed design of the plant. The method is applied to representative toxic gas leakage accidents in a hydrogen production plant by thermochemical Iodine-Sulfur water splitting method coupled to the HTTR gas turbine test plant. Variable parameters are successfully selected for the inputs to uncertainty propagation analysis by sensitivity analysis. Epistemic and aleatory uncertainties for each variable parameter are identified and are propagated using Latin hypercube sampling. The analyses show that the suggested method can successfully characterize and quantify uncertainties in the toxic gas concentration in control room. One important finding is that impact of uncertainty in surface roughness height on toxic gas concentration in control room is significant. The uncertainty is due largely to the simplification of the modeling of obstacles that exists between the reactor building and hydrogen production plant. The results lead us to the conclusion that toxic gas dispersion behavior analysis should combine two evaluation methods: dense gas dispersion model and computational fluid dynamics simulation.